Respuesta :
Answer:
Option (a) is correct.
The value of expression [tex](-m)^{-3}n[/tex] when m = 2 and n = -24 is 3.
Step-by-step explanation:
Given expression [tex](-m)^{-3}n[/tex]
We have to evaluate the value of given expression when m = 2 and n = - 24
Consider the given expression [tex](-m)^{-3}n[/tex],
to find the value of expression at m = 2 and n = -24
Substitute in the expression the values of m and n
[tex]\Rightarrow (-m)^{-3}n=(-2)^{-3}(-24)[/tex]
Using property of exponents, [tex]a^{-x}=\frac{1}{a^x}[/tex]
We get, [tex]\Rightarrow (-2)^{-3}(-24)=\frac{-24}{(-2)^3}[/tex]
Solving further, we get,
[tex]\Rightarrow \frac{-24}{(-2)^3}=\frac{-24}{-2 \times -2 \times -2}[/tex]
On solvine we get [tex]\frac{-24}{-2 \times -2 \times -2}=3[/tex]
Thus, the value of expression [tex](-m)^{-3}n[/tex] when m = 2 and n = -24 is 3.
Thus, option (a) is correct.